2020
DOI: 10.11604/pamj.2020.36.185.22128
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus serological markers among potential blood donors: an evidence of asymptomatic dengue virus transmission in Cameroon

Abstract: Introduction the risk of dengue virus or its antibodies which can be transmitted through blood transfusion by asymptomatic individuals infected, has been a major concern all over the world. Dengue is an endemic disease in sub-Saharan Africa, particularly in Cameroon. The purpose of this study is to determine the frequency of dengue virus (DENV) infection among potential blood donors at Yaounde Jamot Hospital. Methods serum samples were collected from 310 potential adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
4
1
Order By: Relevance
“…The remainder (38.34%) were cases of secondary infection. This result is similar to that reported by who found a seroprevalence of 4.5%, 12.3% and 6.1% for the NS1 antigen, IgM, and IgG antibodies respectively [17]. This also suggests that the serological profile is different between the two populations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The remainder (38.34%) were cases of secondary infection. This result is similar to that reported by who found a seroprevalence of 4.5%, 12.3% and 6.1% for the NS1 antigen, IgM, and IgG antibodies respectively [17]. This also suggests that the serological profile is different between the two populations.…”
Section: Discussionsupporting
confidence: 91%
“…However, the coinfection rate found in this study (14%) is close of that of Yousseu et al (13%) reported in Douala (Cameroon) [14], lower than that of Mustapha et al (44.2%) reported in Abuja (Nigeria) [30] in HIV-patients and higher than that recently documented in febrile patients from the Adamawa region (8.95%) in Cameroon by our research group [18]. Similarly, the dengue mono-infection rate found here is higher than that described by Tchuandom et al (24.8%) in blood donors recruited at the Jamot Hospital in Yaounde [17]. These discrepancies might be explained by the fact that both infections are highly endemic in the East region.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…A lower prevalence was also observed worldwide, such as in China (0.4-5.0 %), Taiwan (0.2 %), Saudi Arabia (5.5%), India (6.0%), Singapore (2.8 %) Mexico (2.0 %) and Australia (0.2 %) [11][12][13][14][15][16][17][18]. In contrast, a higher prevalence was observed in Cameroon (22.9 %) [19]. These differences may be a result of implementation of the control measures to curb DENV outbreaks, the intensity of the outbreak (in an epidemic year), the lower circulation of the virus (non-epidemic year), the circulation of different serotypes, and differences in the sensibility of the screening methods for anti-DENV IgM.…”
Section: Discussionmentioning
confidence: 99%
“…Arboviral diseases constitute a growing international public health threat, especially due to the absence of functional vaccines for some of the diseases, therapeutic drugs, and effective vector control programmes [ 79 ]. In Cameroon, different arboviruses have been reported in febrile and non-febrile patients in different localities in the country [ 21 , 80 82 ]. The most prevalent include dengue, chikungunya, yellow fever, zika, and Rift Valley fever viruses [ 19 , 21 , 30 , 83 91 ].…”
Section: Mosquito-borne Diseases and Pathogens Circulating In Cameroonmentioning
confidence: 99%